Calcitonin Induces Bone Formation by Increasing Expression of Wnt10b in Osteoclasts in Ovariectomy-Induced Osteoporotic Rats - Hsiao, Chen-Yuan; Chen, Tien-Hua; Chu, Tzu-Hui; Ting, Yen-Nien; Tsai, Pei-Jiun; Shyu, Jia-Fwu (Frontiers in Endocrinology, 2020)
Calcitonin is a small peptide hormone secreted from the parafollicular cells of the thyroid gland in response to an increase in serum calcium. The inhibition of osteoclastic resorption is the main mechanism by which calcitonin quickly decreases circulating calcium levels. Although calcitonin pharmacologically acts on osteoclasts to prevent bone resorption, the results of studies on genetically modified animals have shown that the physiological effect of calcitonin is in the inhibition of osteoblastic bone formation. Because the calcitonin receptor is only expressed in osteoclasts, the effect of calcitonin on osteoblasts maybe indirect and mediated via osteoclasts. Wnt ligands are involved in various aspects of skeletal biology, including bone remodeling and endochondral bone formation. Wnt10b has recently been recognized as a clastokine, and is potentially a therapeutic target for treating bone disorders. However, the extent to which Wnt signaling is involved in bone physiology and disease is not yet fully understood. We hypothesize that calcitonin indirectly increases osteoblastic bone formation by inducing Wnt10b expression in osteoclasts. Micro-CT analysis revealed reduced bone loss in calcitonin-treated ovariectomized rats. The serum of animals treated with calcitonin had decreased TRAP5b and CTX-1 but increased osteocalcin, P1NP and Wnt10b. Immunohistochemistry staining showed that the level of Wnt10b in the femur was increased in calcitonin-treated groups as compared with control groups. Hematopoietic mononuclear cells were separated from rat femur and tibia bone marrow, and were induced into osteoclasts following treatment with M-CSF and RANKL. In these cells, immunoconfocal microscopy and Western blot analysis showed that calcitonin induced an increase in Wnt10b expression. In a culture of osteoblasts isolated from neonatal rat calvariae, the calcitonin-treated osteoclast supernatant showed an increase in mineralization, as indicated by ALP and alizarin red staining. Taken together, these results indicate that calcitonin induces bone formation by increasing the expression of Wnt10b in osteoclasts in ovariectomy-induced osteoporotic rats. The present study provides in-depth information about the effects of calcitonin on bone remodeling and will thus help in the development of future potential therapeutic strategies for postmenopausal osteoporosis.